2020
DOI: 10.1186/s12889-019-7934-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after hospital admission for heart failure: improvement over time, equally strong in women as in men

Abstract: Background: To assess the trend in age-and sex-stratified mortality after hospitalization for heart failure (HF) in the Netherlands. Methods: Two nationwide cohorts of patients, hospitalized for new onset heart failure between 01.01.2000-31.12.2002 and between 01.01.2008-31.12.2010, were constructed by linkage of the Dutch Hospital Discharge Registry and the National Cause of Death registry. 30-day, 1-year and 5-year overall and cause-specific mortality rates stratified by age and sex were assessed and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
26
1
1
Order By: Relevance
“…So was the percentage of studies that included patients who were hospitalized due to HF (e.g., unstable HF patients) lower in studies who did not report a beneficial effect of structured telephone support or non-invasive remote monitoring on the all-cause mortality, all-cause hospitalization, or HF-related hospitalization rates. Hospitalization for HF is associated with an increased risk for mortality as well as rehospitalizations [ 5 , 74 ]. In these unstable HF patients, non-invasive remote monitoring has the largest potential to improve their clinical outcomes and reduce the HF-related hospitalization rates.…”
Section: Reasons For Inconsistent Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So was the percentage of studies that included patients who were hospitalized due to HF (e.g., unstable HF patients) lower in studies who did not report a beneficial effect of structured telephone support or non-invasive remote monitoring on the all-cause mortality, all-cause hospitalization, or HF-related hospitalization rates. Hospitalization for HF is associated with an increased risk for mortality as well as rehospitalizations [ 5 , 74 ]. In these unstable HF patients, non-invasive remote monitoring has the largest potential to improve their clinical outcomes and reduce the HF-related hospitalization rates.…”
Section: Reasons For Inconsistent Resultsmentioning
confidence: 99%
“…Timely detection of congestion due to HF can prevent HF-related hospitalization, reduce the overall burden on health care resources, and improve patient outcomes [ 5 , 6 ]. Remote monitoring could be a crucial tool for the early detection of deterioration of HF.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional risk factors like diabetes, hypertension, smoking, and hyperlipidemia are well-recognized for predicting mortality with cardiovascular diseases (3,4). Studies have also reported that albuminuria not only is an independent risk factor for the development of cardiovascular disease but also acts as a biomarker for predicting mortality in such patients (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on extent of the decline in left ventricular ejection function (LVEF), HF is typically classified into heart failure with preserved ejection fraction (HFpEF) and with reduced ejection fraction (HFrEF) types. However, patients with HF have poor prognosis regardless of the LVEF, with a poor survival rate of < 50% within 5 years after the first hospitalization ( Tribouilloy et al, 2008 ; Buddeke et al, 2020 ). In addition, almost half of the HF patients suffer from fatigue, breathlessness, edema or arrhythmias, which significantly reduces the quality of life ( Gohler et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%